Implementation and initial calibration of carbon-13 soil organic matter decomposition in the Yasso model - Mäkelä, Jarmo; Arppe, Laura; Fritze, Hannu; Heinonsalo, Jussi; Karhu, Kristiina; Liski, Jari; Oinonen, Markku; Straková, Petra; Viskari, Toni (Copernicus GmbH, 2022)
Soils account for the largest share of carbon found in terrestrial ecosystems, and their status is of considerable interest for the global carbon cycle budget and atmospheric carbon concentration. The decomposition of soil organic matter depends on environmental conditions and human activities, which raises the question of how permanent are these carbon storages under changing climate. One way to get insight into carbon decomposition processes is to analyse different carbon isotope concentrations in soil organic matter. In this paper we introduce a carbon-13-isotope-specific soil organic matter decomposition add-on into the Yasso soil carbon model and assess its functionality. The new 13C-dedicated decomposition is straightforward to implement and depends linearly on the default Yasso model parameters and the relative carbon isotope (13CC) concentration. The model modifications are based on the assumption that the heavier 13C atoms are not as reactive as 12C. The new formulations were calibrated using fractionated C, 13C and δ13 measurements from litterbags containing pine needles and woody material, which were left to decompose in natural environment for 4 years. The introduced model modifications considerably improve the model behaviour in a 100-year-long simulation, where modelled δ13 is compared against fractionated peat column carbon content. The work presented here is a proof of concept and enables 13C to be used as a natural tracer to detect changes in the underlying soil organic matter decomposition.
Keywords: carbon; decomposition; organic matter; soil; Yasso model